In-hospital costs of diabetic foot infection at a national referral hospital in Jakarta, Indonesia - Fitrianingsih; Rani Sauriasari; Em Yunir; Agusdini Banun Saptaningsih (Heliyon)
Aims: To determine the in-hospital costs of patients with diabetic foot problems who either require or do not require amputation. Methods: We conducted a retrospective cross-sectional study of 213 subjects with low, moderate and high ulcer grades from January 2019 to December 2022 at a national referral hospital in Jakarta, Indonesia. Data were taken from the medical admissions record unit, electronic health records (EHR), hospital integrated system (HIS) and the foot registry system in the metabolic endocrine division, in relation to diabetic foot infection (DFI) as the primary or secondary diagnosis. We analysed data referring to patient characteristics, in-hospital costs and length of stay (LOS), with further comparison based on amputation status. Results: The total DFI costs were estimated at IDR 13.833 billion (median IDR 51.225 [min – max; 10.309–507.281) million]). The total costs were estimated at IDR 64.95 ± 50.89 million per patient. All cost variables were driven by intervention costs estimated at IDR 5.176 billion (median IDR 19.676 [min – max; 1.245–136.348) million per patient). Daily costs were IDR 3.281 million per patient per day. The total treatment costs for amputation and non-amputation were IDR 6.99 billion (median IDR 61.398 (18.785–268.768) million) and IDR 6.842 billion (median IDR 45.016 (10.309–507.282) million, respectively. The average LOS was 19.79 ± 10.77 days per DFI episode, which did not differ significantly between the amputation and non-amputation groups (p > 0.176) but not for total costs (p < 0.003). DFI is associated with high costs and long-term hospital stays. Conclusions: Our study provides evidence on in-patient hospital costs by capturing the real costs of DFI treatment, with the total treatment costs for amputation being higher than for non-amputation. This information might benefit for health practitioners in clinical practice improvements and policy adjustments, including INA-CBGs tariff for DFI patients.